Seasonal Changes in Dissolved Organic Matter Composition in a Patagonian Fjord Affected by Glacier Melt Inputs - Marshall, Matthew G.; Kellerman, Anne M.; Wadham, Jemma L.; Hawkings, Jon R.; Daneri, Giovanni; Torres, Rodrigo; Pryer, Helena V.; Beaton, Alexander; Ng, Hong Chin; Urra, Alejandra; Robinson, Laura F.; Spencer, Robert G. M. (Frontiers in Marine Science, 2021)
Biogeochemical processes in fjords are likely affected by changes in surrounding glacier cover but very little is known about how meltwater directly influences dissolved organic matter (DOM) in fjords. Moreover, the data available are restricted to a handful of northern hemisphere sites. Here we analyze seasonal and spatial variation in dissolved organic carbon (DOC) concentration and DOM composition (spectrofluorescence, ultrahigh resolution mass spectrometry) in Baker-Martinez Fjord, Chilean Patagonia (48°S), to infer the impacts of rapid regional deglaciation on fjord DOM. We show that surface layer DOC concentrations do not vary significantly between seasons, but DOM composition is sensitive to differences in riverine inputs. In summer, higher protein-like fluorescence reflects increased glacial meltwater inputs, whilst molecular level data show weaker influence from marine DOM due to more intense stratification. We postulate that the shifting seasonal balance of riverine and marine waters affects the supply of biolabile peptides and organic nitrogen cycling in the surface layer. Trends in DOM composition with increasing salinity are consistent with patterns in estuaries (i.e. preferential removal of aromatic compounds and increasing relative contribution of unsaturated and heteroatom-rich DOM from marine sources). Preliminary estimates also suggest that at least 10% of the annual organic carbon stock in this fjord is supplied by the four largest, glacially fed rivers and that these inputs are dominated by dissolved (84%) over particulate organic carbon. Riverine DOC may therefore be an important carbon subsidy to bacterial communities in the inner fjord. The overall findings highlight the biogeochemical sensitivity of a Patagonian fjord to changes in glacier melt input, which likely has relevance for other glaciated fjords in a warming climate.